(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
In this article, Uzbek agricultural terminology is systematically analyzed based on semantic field theory. During the research, the lexico-semantic structure of agricultural terms, the principles of their semantic grouping, and internal systemic connections are revealed. Terms are studied based on paradigmatic and syntagmatic relationships, and the main semantic fields and their constituent units are described. The central and peripheral layers of agricultural terminology, its relationship with common vocabulary, and sectoral hierarchy are also highlighted. The research results serve as a solid theoretical and practical basis for systematizing agricultural terminology, its scientific classification, and creating a sectoral thesaurus (a special terminological vocabulary system built on semantic connections).